Asthma status is an independent risk factor for herpes zoster in children: a population-based cohort study. (18th August 2017) - Chen, Su-Jing; Huang, Kuang-Hua; Tsai, Wen-Chen; Lin, Cheng-Li; Cheng, Yih-Dih; Wei, Chang-Ching
Abstract: Backgrounds: Literatures regarding the effects of childhood asthma on the risk of herpes zoster (HZ) is very limited. The aim of this study is to investigate the risks of children developing HZ with asthma. Methods: From the National Health Insurance Research Database, we identified 300, 649 patients who had asthma between 2000 and 2007 as an asthma cohort. We identified another matched non-asthma cohort. All subjects were followed until the end of 2008. A Cox model was used to estimate the association of asthma on the risk of HZ. Results: Asthma cohort had significantly higher risk of developing HZ than the comparison cohort (HR=1.15; 95 % CI =1.06-1.26). However, compared to those without regular controller, asthma cohort with regular inhaled corticosteroid (ICS) treatment had slightly increased risk for HZ (HR=1.14; 95% CI=1.01-1.27) but decreased risk for HZ in those with regular combined ICS and Montelukast (HR=0.83; 95% CI=0.69-0.98). Uncontrolled asthma with more than 3-4 times ED visits and admissions per year had 3.72 (CI =1.86-7.47) and 20.5 (CI =10.2-41.2) greater risks for HZ than those without asthma, respectively. Conclusions: Asthma poses an increased risk of zoster, therefore control of asthma is important to minimize risk of HZ.